Exploring the cytotoxic activity of new phenanthroline salicylaldimine Zn(II) complexes - Matos, Cristina P. (2020)
Zinc(II) complexes bearing N-salicylideneglycinate (Sal-Gly) and 1,10-phenanthroline (phen) or phenanthroline derivatives [NN= 5-chloro-1,10-phenanthroline, 5-amine-1,10-phenanthroline (amphen), 4,7-diphenyl-1,10-phenanthroline (Bphen) and 5,6-epoxy-5,6-dihydro-1,10-phenanthroline] are synthesized. Complexes formulated as [Zn(NN)(2)(H2O)(2)](2+) (NN = phen and amphen), are also prepared. The cytotoxicity of the compounds is evaluated towards a panel of human cancer cells: ovarian (A2780), breast (MCF7) and cervical (HeLa), as well as non-tumoral V79 fibroblasts. All compounds display higher cytotoxicity than cisplatin (IC50 = 22.5 +/- 5.0 mu M) towards ovarian cells, showing IC50 values in the low micromolar range. Overall, all compounds show higher selectivity for the A2780 cells than for the non tumoral cells and higher selectivity indexes (IC50(V79)/IC50(A2780) than cisplatin. [Zn(Sal-Gly)(NNI(H2O)] complexes induce caspase-dependent apoptosis in A2780 cells, except [Zn(Sal-Gly)(Bphen)(H2O)], one of the most cytotoxic of the series. The cellular uptake in the ovarian cells analyzed by Inductively Coupled Plasma mass spectrometry indicates different Zn distribution profiles. Transmission electronic microscopy shows mitochondria alterations and apoptotic features consistent with caspase activationells incubated with EZn(Sal-Gly)(amphen)(H2O)] present additional nuclear membrane alterations in agreement with significant association with the nucleus. The increase of reactive oxygen species and lipid peroxidation forms could be related to apoptosis induction. [Zn(NN)(2)(H2O)(2)](2+) complexes have high ability to bind DNA through intercalation/groove binding, and circular dichroism data suggests that the main type of species that interact with DNA is [Zn(NN)](2+). Studies varying the % of fetal bovine serum (1-15%) in cell media show that albumin binding decreases the complex activity, indicating that distinct speciation of Zn- and phen-containing species in cell media may affect the cytotoxicity.